2021
DOI: 10.1002/ece3.8443
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of light‐demanding tree species in the Yangambi rainforest (Democratic Republic of Congo)

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 103 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…The regular distribution of individuals across the park was not found for any single tree species. It is important to note that regular distribution occurs when there is a strong antagonistic relationship between spatial objects, or in the case of artificial placement (Luambua et al, 2021). Considering that a large part of the park plantation arose artificially, regular placement of woody plants would be quite expected.…”
Section: Discussionmentioning
confidence: 99%
“…The regular distribution of individuals across the park was not found for any single tree species. It is important to note that regular distribution occurs when there is a strong antagonistic relationship between spatial objects, or in the case of artificial placement (Luambua et al, 2021). Considering that a large part of the park plantation arose artificially, regular placement of woody plants would be quite expected.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregation is common in tropical trees (e.g. Picard et al, 2009;Plotkin et al, 2002;Réjou-Méchain et al, 2011;Traissac & Pascal, 2014) and different factors can promote species aggregation (Luambua et al, 2021) such as: i) variation in local site characteristics and site history (spatial heterogeneity); ii) competition for light leading to regeneration of clustered offspring in tree gaps (mostly for light demanding-species); iii) spatially limited seed dispersal; iv) biotic factors (intra-or intercompetition and facilitation). Clustered distribution of this anemochorous species in evergreen (site C) and semideciduous forests (site A) suggested that aggregation was strongly driven by spatially limited seed dispersal (as discussed below) and light-requirements for the growth of seedlings.…”
Section: Fine-scale Spatial Distribution and Genetic Structure Also V...mentioning
confidence: 99%
“…Regeneration success of light-demanding species also depends on intrinsic factors such as the mating system and the extent of seed and pollen dispersal (Hardy et al, 2019), processes affecting in turn the demographic, spatial and genetic structures of tree populations (Luambua et al, 2021;Sola et al, 2022). Most tropical tree species are allogamous but self-compatible and occur at low population density (Duminil et al, 2016a;Duminil et al, 2016b;Hardy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by exceptional biodiversity and vegetation dominated by dense and humid forest (Toirambe, 2011). This landscape has a tropical climate, Af type according to Köppen's classification (Luambua et al, 2021). This landscape extends over 225,000 ha of BRY, and includes enclaves in buffer zone and others villages located within 30 km of the PA border (Kipute et al, 2021).…”
Section: Study Locationmentioning
confidence: 99%